SEMANTIC-STRUCTURE OF POLYSEMANTIC WORDS IN MEMORY TEXTS (Scientific journal of the Fergana State University, 2023)
The article ehamines the semantic and their structure of polysemantic words in memory texts. According to the opposition of the meanings of the polysemantic lexeme, the following types of polysemy (Associati polysemia and associative-content polysemy) are illuminated through multi-meaning words in memory texts. In addition, in polesemias, the meaning is linked from both the associative and the content side, and their semantic structure is similar, and it is started to reveal through analysis that the sememes contained in one lexeme contain a large amount of common, identical semes.